Urban Power Grid Electromagnetic Loop Breaking Method Based on Fast Network Partition Algorithm - Feng, Zhang; Guang, Chen; Ji-Yuan, Mu; Xin, Jin; Yi-Fei, Pan; Ming-Chun, Yin; Ming-Da, He; De-Dao, Du (2018 China International Conference on Electricity Distribution (CICED), 2018)
The overrun problem of the short circuit current has been restricting the development of large urban power grid. Breaking up the high and low voltage electromagnetic loop network("loop breaking" for short) is an effective solution. However, in recent years, the uncertainty of power grid planning and the flexible requirements of system operation are sharply increased, which makes the loop breaking scheme has to be rolling adjusted in time. But the traditional loop breaking analysis methods are difficult to meet the timeliness. In the paper, a fast loop breaking method based on the network partition algorithm is provided. Its advantage is using clustering method to replace the traversal search of transmission line breaking combination. In this way, the Non-deterministic Polynomial (NP) complete problem can be avoid. The time consuming can be reduced to less than 1% of the traditional method. Efficiency improved significantly. The method is double layer structure: the first layer is grouping analysis of the high to low voltage downlink buses, and the second layer is network partition based on the grouping results. Case study shows that the effective loop breaking schemes of a real large urban power grid can be obtain in minutes. Therefore, it can be applied to the practical engineering.